2016
DOI: 10.18632/oncotarget.14198
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of miR-34b and androgen receptor pathway regulate prostate cancer aggressiveness between African-Americans and Caucasians

Abstract: African-Americans are diagnosed with more aggressive prostate cancers and have worse survival than Caucasians, however a comprehensive understanding of this health disparity remains unclear. To clarify the mechanisms leading to this disparity, we analyzed the potential involvement of miR-34b expression in African-Americans and Caucasians. miR-34b functions as a tumor suppressor and has a multi-functional role, through regulation of cell proliferation, cell cycle and apoptosis. We found that miR-34b expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…MicroRNAs have been implicated in racial disparity in AAs when compared with Caucasians (9,(37)(38)(39). In this direction, Wang et al reported that AA-specific/-enriched miRNA-mRNA pairings such as miR-133a/MCL1, miR-513c/STAT1, miR-96/FOXO3A, miR-145/ITPR2 and miR-34a/PPP2R2A may play a critical role in the activation of oncogenic pathways in AA PCa cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs have been implicated in racial disparity in AAs when compared with Caucasians (9,(37)(38)(39). In this direction, Wang et al reported that AA-specific/-enriched miRNA-mRNA pairings such as miR-133a/MCL1, miR-513c/STAT1, miR-96/FOXO3A, miR-145/ITPR2 and miR-34a/PPP2R2A may play a critical role in the activation of oncogenic pathways in AA PCa cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…It is widely recognized that when compared to white men, African American men are more likely to develop PCa, tend to be diagnosed at a younger age, exhibit higher prostate-specific antigen (PSA) levels, and demonstrate more advanced or metastatic disease at diagnosis (8)(9)(10)(11)(12). Besides, African American men are four times more likely to develop metastatic PCa (mPCa) than white men and more than twice as likely to die from PCa (13)(14)(15)(16)(17)(18)(19). It is of vital importance to continue research on racial disparity of PCa to better understand the disease and improve the survival outcomes of African American men.…”
Section: Introductionmentioning
confidence: 99%
“…Let-7c indirectly represses AR activity by targeting c-Myc, which acts as a transcription factor for the AR gene [ 65 , 66 ]; (B) AR mRNA—miRs target AR directly through binding to microRNA response elements in its transcript. Most microRNAs target the 3′UTR [ 4 , 24 , 31 , [38] , [39] , [40] , [41] , [42] , [43] , 45 , 46 ], but interactions with the coding region and 5′UTR have also been reported [ 4 , 56 ]; (C) AR-mediated transcription of target genes—miRs modulate AR indirectly by targeting cofactors, regulators or effectors of AR activity [ 19 , 63 , 64 ]; (D) AR competitive endogenous RNAs (ceRNAs) —AR is regulated by ceRNAs containing microRNA response elements (MREs) for AR-targeting miRs. For example, PlncRNA-1 protects AR from miR-mediated repression.…”
Section: Mir Regulation Of the Androgen Signalling Axismentioning
confidence: 99%